Dynamic recrystallization of quartz in veins in sandstones of metagenesis zone (Kular district, Yakutia) - O. A. Sustavov (Известия высших учебных заведений: Геология и разведка, 2019)
Bulging recrystallization (BR) has been considered in the deformed quartz veins in the lower Triassic sandstones of the metagenesis zone in the North-Western part of the Kular district, Yakutia. BR is characterized by the formation of sutured boundaries of individuals during the crystalloplastic deformation of quarz. To these boundaries, the recrystallization grains are confined, the size of which (in this case, 0,01—0,02 mm) corresponds to the size of the teeth at the boundaries of individuals. Such fine recrystallization grains can fix with their formation the peak crustal stresses arising up during deformation of the continental crust near the brittle-plastic transition. Inside the individuals, BR is accompanied by recrystallization along the microshears and deformation bands with the leading role of progressive rotation of subgrains. BR in vein quartz occurs during the formation of the pressure solution cleavage in the host sandstones, and therefore the combination of the pressure solution cleavage in the sandstones of the metagenesis zone and BR in vein quartz can be considered as structural paragenesis.